Beatrice, a degree in Physics at the age of 19 at the time of Garbasso - Mazzoni, Massimo; Righini, Alberto; Mazzinghi, Piero (Il Colle di Galileo, 2022)
Thanks to extensive archive research, aimed at celebrating the 100th anniversary of the inauguration of the Institute of Physics at Arcetri, we have reconstructed the panorama of the period complete with the profiles of its key figures: professors, young researchers and students. The latter include a brilliant young woman, Beatrice Crinò, whose curriculum studiorum and career profile deserve some in-depth study, together with her family and cultural background.